Electron beam irradiation effect on the physicochemical characteristics of municipal excess sludge. (March 2021) - Li, Xin; Jin, Wenjie; Du, Yan; Tan, Zhouliang; Liu, Ruiyuan; Xiao, Rongqing; Wang, Jufang; Wang, Jie; Zhou, Libin
Abstract: This work detailed the characteristics of municipal excess sludge irradiated by an electron beam for land application. From 5 kGy to 20 kGy, the release of soluble organic matter, nitrogen, and phosphorus substances in the sludge extract were markedly improved, and they exhibited different radiation susceptibility to free radicals and molecular products of the electron beam irradiation. The results indicated that, with the same sludge thickness, both irradiation products can efficiently react with organic matters. A further irradiation effect was caused majorly by molecular products, and an unsuitable thickness can produce a negative irradiation effect. Moreover, although an increased dose can cause an increase of Cu and Zn ions in the extract, the Cd and Pb contents were reduced by 35.71% and 20.97%, respectively, after 20 kGy of irradiation. In addition, the result of Fourier transform infrared spectra suggested that the electron beam irradiation has a significant impact on the organic matter in the sludge. Highlights: The release of nutrient substances from irradiated sludge had different radiation susceptibility to the EB irradiation products. The irradiation dose rate could also affect the characteristics of the irradiated sludge significantly. An inappropriate sludge thickness would reduce the release of nitrogenous substances. The results of extract indicated that the irradiation could reduce the content of Cd and Pb in the sludge.